Dialektika ontologis “miskin dalam roh” dan “kaya di hadapan Allah”: Reevaluasi filologis Matius 5:3 dan Lukas 12:21 terhadap terjemahan LAI - Rimun, Robinson (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
Matthew 5:3 serves as the theological prolegomenon to the Ser-mon on the Mount and undergoes semantic shifts in Indonesian translation. This article critically evaluates the Indonesian Bible Society's (LAI) translation of